Improving Legal Awareness of Islamic Families: Rights and Obligations of Husband and Wife in Handio Village - Nasution, Nur Jannah; Nasution, Ilham Azhari; SIiregar, Mhd. Halomoan; Hasibuan, Linda Khotmaidah; Butar-Butar, Halimah (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to enhance the legal awareness of Islamic families among married couples in Handio Village, particularly concerning their rights and obligations. The lack of understanding of legal aspects in marriage often serves as a trigger for domestic conflicts. This research employs a qualitative descriptive method. Data were collected through in-depth interviews with married couples, religious leaders, and community figures, as well as through observation. The findings reveal that most married couples in Handio Village have a limited understanding of their rights and obligations according to Islamic law and marriage legislation. This has led to a lack of justice and responsibility within households. Through counseling programs and interactive discussions, there was a significant improvement in their legal awareness. The program successfully fostered the understanding that family harmony is not only built on love but also on a fair comprehension and execution of mutual rights and responsibilities.